Android-Based E-Module Design in Electric Motor Installation Lessons at SMK Negeri Agriculture, Serang City - Muhamad Faizz; Irwanto Irwanto; Bagus Dwi Cahyono (Jurnal Pembelajaran Fisika, 2022)
This study aims to: (1) determine the process of designing Android-based                  E-Modules; and (2) knowing the feasibility of Android-Based E-Modules in helping class XI students understand the material for Electric Motor Installation at the Agriculture State Vocational School in Serang City. This research is a type of Research and Development research with reference to the Lee & Owens model (2004). The subjects of this study included 3 lecturers, 3 teachers, and students of class XI in the Department of Electrical Power Installation Engineering, Agriculture State Vocational School, Serang City. Data collection methods in this study are tests and non-tests. Based on the results of the Android-Based E-Module trial that was developed it is suitable for use as teaching materials, where the acquisition of an overall average aspect score by media experts is 3.59 in the very good category, the average overall aspect score by material experts is 3.50 in the category very good and the overall average score of aspects  by student responses to the E-Module is 3.78 in the very good category. Evaluation of students shows the results of the percentage of success of 83.15% which fall into the category of high success criteria.Keywords: design; e-module; and electric motor.DOI: http://dx.doi.org/10.23960/jpf.v10.n2.202202